Borderline Personality Features and Harmful Dysregulated Behavior: The Mediational Effect of Mindfulness. Issue 9 (4th March 2013) - Wupperman, Peggilee; Fickling, Melissa; Klemanski, David H.; Berking, Matthias; Whitman, Jeannie B.
<x xml:space="preserve">Abstract</x> Objectives The current preliminary study investigated whether deficits in mindfulness (awareness, attentiveness, and acceptance of the present experience) may underlie the relationship of borderline personality disorder (BPD) features to self‐injury and overall acts of harmful dysregulated behavior. Method Nonparametric bootstrapping procedures were used to examine theoretical relationships among variables in a psychiatric sample of adults (N = 70). Participants were asked to imagine themselves in distress‐inducing situations and then write what they would actually do to decrease distress in such situations. Results As hypothesized, mindfulness statistically mediated the relationship of BPD features to reported acts of (a) self‐injury and (b) overall harmful dysregulated behaviors. Conclusions Difficulties in the ability to be aware, attentive, and accepting of ongoing experience may play a role in the relationship of BPD features to harmful dysregulated behaviors. Future research should clarify potential reciprocal effects between BPD features and mindfulness with prospective, multioccasion designs.